Kontribusi Theologia Yohanes Calvin tentang Hubungan Gereja dan Negara sebagai Pola Misi - Ruseniati (Jurnal Missio Cristo, 2020)
Abstract: How is the christian’s opinion? Should we obey more to the state or to the church? Of course, we must always obey to God, but this does not mean that we neglect our obedience to the social-human institutions, such as a state. Calvin said “the State institution it self is actually a manifestation of our human social nature established by God. In their respective areas, the state and the church are two autonomous entities. However, as public institutions they are related to each other, thus to a certain extent they are not opposed to each other.” In this case, the church has the obligation to support and assist the state, that means, the church cooperates with the state (i.e. the government) to realize the society welfare. Therefore, relation between the church with the state can be applied as the pattern of mission in the church ministry. It’s similar with Calvin’s statement in his theology about the practice of church ministry in the society community.